Effect of compression garments on physiological responses after uphill running - Struhár, I.; Kumstát, M.; Moc Králová, D. (Journal of Human Kinetics, 2018)
Limited practical recommendations related to wearing compression garments for athletes can be drawn from the literature at the present time. We aimed to identify the effects of compression garments on physiological and perceptual measures of performance and recovery after uphill running with different pressure and distributions of applied compression. In a random, double blinded study, 10 trained male runners undertook three 8 km treadmill runs at a 6% elevation rate, with the intensity of 75% VO2max while wearing low, medium grade compression garments and high reverse grade compression. In all the trials, compression garments were worn during 4 hours post run. Creatine kinase, measurements of muscle soreness, ankle strength of plantar/dorsal flexors and mean performance time were then measured. The best mean performance time was observed in the medium grade compression garments with the time difference being: medium grade compression garments vs. high reverse grade compression garments. A positive trend in increasing peak torque of plantar flexion (60o·s-1, 120o·s-1) was found in the medium grade compression garments: a difference between 24 and 48 hours post run. The highest pain tolerance shift in the gastrocnemius muscle was the medium grade compression garments, 24 hour post run, with the shift being +11.37% for the lateral head and 6.63% for the medial head. In conclusion, a beneficial trend in the promotion of running performance and decreasing muscle soreness within 24 hour post exercise was apparent in medium grade compression garments.